Removal of Rhodamine B Dye by Plasma Jet Oxidation Process - Le, Quynh Xuan Thi; Tran, Hong Quan; Trinh, Thu Ha; Dao Nguyen, Thuan (Communications in Physics, 2021)
Recently, nonthermal atmospheric pressure plasma has been developed as a novel tool in removal of water pollutants. Rhodamine B dye, widely used in textiles and biology, is toxic to both humans and animals, hence removing residual Rhodamine B in solution is necessary. In this work, we have setup a cold plasma jet system and used it to effectively remove Rhodamine B in the solution. We have shown that the main oxidation substance responsible to remove Rhodamine B is the hydroxyl radical (•OH). By studying the effect of the hydrogen peroxide (H2O2) concentration in the initial and later was produced in the solution, the plasma power, and the Ar gas flow speed on the dye remove rate, we have identified 2 main reaction pathways to generate hydroxyl radical (•OH). Both of these reaction pathways involve high-energy electrons interacting with water and O2 in the solution and in the ambient air. Our work provides important information to understand the mechanism of dye removal by cold plasma treatment